2020
DOI: 10.3390/plants9040521
|View full text |Cite
|
Sign up to set email alerts
|

Severe Plastid Genome Size Reduction in a Mycoheterotrophic Orchid, Danxiaorchis singchiana, Reveals Heavy Gene Loss and Gene Relocations

Abstract: Danxiaorchis singchiana (Orchidaceae) is a leafless mycoheterotrophic orchid in the subfamily Epidendroideae. We sequenced the complete plastome of D. singchiana. The plastome has a reduced size of 87,931 bp, which includes a pair of inverted repeat (IR) regions of 13,762 bp each that are separated by a large single copy (LSC) region of 42,575 bp and a small single copy (SSC) region of 17,831 bp. When compared to its sister taxa, Cremastra appendiculata and Corallorhiza striata var. involuta, D. singchiana sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Comparative analysis of plastomes showed that C. sinensis has one small inversion occurred in the LSC region. However, the larger inversions appear in D anxiaorchis singchiana ( Lee et al., 2020 ), C. maculata var. maculata ( Barrett et al., 2014 ) and C. maculata ( Kim et al., 2020 ), which had been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Comparative analysis of plastomes showed that C. sinensis has one small inversion occurred in the LSC region. However, the larger inversions appear in D anxiaorchis singchiana ( Lee et al., 2020 ), C. maculata var. maculata ( Barrett et al., 2014 ) and C. maculata ( Kim et al., 2020 ), which had been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Flower gardening traditionally employs Phalaenopsis hybrid cultivars. Only one diploid cultivar has been documented, whereas over 80% of tetraploid cultivars have 76 chromosomes (Lee S. Y. et al, 2020). The domination of commercial tetraploid cultivars demonstrates the relevance of polyploidy in the development of better Phalaenopsis cultivars.…”
Section: Genome Size and Ploidy Analysis Of The Orchidmentioning
confidence: 99%
“…The comparative genomics of 12 tribe Neottieae orchids indicated that genes related to the NAD(P)H dehydrogenase complex, photosystems, and RNA polymerase were functionally lost many times (Feng et al, 2016). A phylogenetic analysis of 26 full plastome sequences from Epidendreae suggested that photosynthesis-related genes such as the atp complex had undergone severe gene loss (Lee S. Y. et al, 2020). Numerous investigation have identified evidence of fast plastome degradation in heterotrophic orchids based on the accumulation of pseudogenes and substantial deletions (Barrett and Kennedy, 2018;Barrett et al, 2019;Kim et al, 2019).…”
Section: Sequencing and Evolution Of The Chloroplast Genome In Orchidmentioning
confidence: 99%
“…Full mycoheterotrophy has evolved repeatedly across land plants with associated losses of photosynthesis. Over half of the origins are thought to have occurred in Orchidaceae (Merckx and Freudenstein, 2010; Merckx et al, 2013), but to date only a subset of the independent transitions to heterotrophy in this family have been characterized with fully sequenced plastid genomes (Delannoy et al, 2011; Logacheva et al, 2011; Barrett and Davis, 2012; Schelkunov et al, 2015; Feng et al, 2016; Huo et al, 2018; Barrett et al, 2019; Kim et al, 2019; Kim et al, 2020; Lee et al, 2020; Z.‐H. Li et al, 2020).…”
mentioning
confidence: 99%
“…Full mycoheterotrophy has evolved repeatedly across land plants with associated losses of photosynthesis. Over half of the origins are thought to have occurred in Orchidaceae (Merckx and Freudenstein, 2010;Merckx et al, 2013), but to date only a subset of the independent transitions to heterotrophy in this family have been characterized with fully sequenced plastid genomes (Delannoy et al, 2011;Logacheva et al, 2011;Barrett and Davis, 2012;Schelkunov et al, 2015;Feng et al, 2016;Huo et al, 2018;Barrett et al, 2019;Kim et al, 2019;Kim et al, 2020;Lee et al, 2020;Z.-H. Li et al, 2020). Sequenced plastid genomes of mycoheterotrophic plants can provide useful phylogenetic information and insights into patterns of genome evolution and changes in selection with the loss of photosynthesis (e.g., Barrett and Davis, 2012;Barrett et al, 2014;Wicke et al, 2016;Graham et al, 2017).…”
mentioning
confidence: 99%